Pentoxifylline Enhances Sperm Quality, Reduces Oxidative Stress in Semen, and Decreases Sperm DNA Damage in Men with Asthenozoospermia Undergoing Assisted Reproductive Technology - Oumaima Ammar; Marwa Ben Ali Gannoun; Tesnim Ajina; Assila Hadj Ali; Manel Boussabbeh; Amira Sallem; Zohra Haouas; Mariarosaria Di Tommaso; Meriem Mehdi (Oxygen)
Oxidative stress (OS) contributes to poor sperm parameters and increased sperm DNA fragmentation (sDF), yet effective therapeutic strategies remain limited. This study aimed to evaluate the in vitro efficacy of pentoxifylline (PTX) in improving sperm motility and reducing OS and sDF in men with isolated asthenozoospermia. Thirty semen samples from patients with asthenozoospermia were processed using density gradient centrifugation. Each sample was divided into two aliquots: one treated with PTX at a dose of 3.6 mM and the other without PTX treatment. The sperm viability and motility were assessed at 30 min, 1 h, 2 h, and 24 h post-treatment. OS was evaluated using nitro blue tetrazolium staining and a chemiluminescence assay. sDF was assessed using the alkaline Comet assay. The sperm samples treated with PTX, compared to the controls, exhibited a significant increase in total sperm motility (71.8 ± 23.03% versus 47.47 ± 4.88%, respectively; p < 0.0001). However, no significant difference was observed in the sperm viability. PTX treatment significantly reduced ROS production and sDF levels compared to controls (p < 0.01). These findings suggest that in vitro PTX supplementation enhances sperm motility and reduces the nuclear sperm injury associated with seminal ROS production. Therefore, PTX supplementation in vitro may be beneficial in assisted reproductive technology procedures involving men with asthenozoospermia.